EVALUASI PENYIMPANAN OBAT DAN ALAT KESEHATAN DI APOTEK RESTU FARMA - Muhammad Afqary; Febi Ishfahani; M. Tirta Rachman Mahieu (Sekolah Tinggi Teknologi Industri dan Farmasi Bogor, 2018)
Storage is one of important process in the management of drug and medical devices.This study aims to evaluate the storage system of drug and medical devices in the Restu Farma Pharmacy. This is a descriptive research which carried on by direct observation and interview. This research was evaluate arrangement of drugs and medical devices in Restu Farma Pharmacy. This research show that in Restu Pharma Pharmacy the drug and medical devices were arranged by type of drugs (tablets, syrups, intervereous liquid and injection). The Restu Pharma Pharamcy‟s warehouse was as the drug and medical devices in Restu Pharma Pharmacy ware house was arrange by type of drugs (tablets, syrups, intervereous liquid and injection).The storage in the warehouse at 75% and the service room at 85% is [compliance with Permenkes No. 73 of the years 2016 about standard of pharmaceutical care at pharmacy.]